2018
DOI: 10.1111/joor.12665
|View full text |Cite
|
Sign up to set email alerts
|

Single puncture versus standard double needle arthrocentesis for the management of temporomandibular joint disorders: A systematic review

Abstract: The aim of this systematic review was to investigate the current evidence in order to assess the efficacy of single puncture arthrocentesis vs standard double needle arthrocentesis in the management of temporomandibular joint(TMJ) disorders. An electronic search of the PubMed, Scopus, Cochrane CENTRAL and Google Scholar databases was performed to identify English studies published up until October 2017. Eligible studies were selected based on inclusion criteria and included randomised controlled trials(RCTs) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The article of Senturk et al focuses mainly on the surgeons’ perspective and lacks details on the patient evaluation. Even a meta-analysis by Nagori et al 14 analyzed 5 trials on these techniques and found that both techniques were equally significant in TMJ disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The article of Senturk et al focuses mainly on the surgeons’ perspective and lacks details on the patient evaluation. Even a meta-analysis by Nagori et al 14 analyzed 5 trials on these techniques and found that both techniques were equally significant in TMJ disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on patients with painful TMJ have implicated the presence of eicosanoids like PGE 2 and leukotriene B 4 as the reason for arthralgia 25 . In this context, arthrocentesis is thought to improve outcomes of TMDs by flushing out inflammatory mediators and reducing the joint vacuum thereby improving the lubrication of the joint 26 . To supplement the efficacy of the procedure, clinicians have also injected several drugs at the end of TMJ arthrocentesis like corticosteroids, sodium hyaluronate, platelet‐rich plasma, and analgesics 5‐7 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, many researchers have described their experience with their procedure for the management of various temporomandibular joint disorders (TMDs). 2 Arthrocentesis is usually employed as the first invasive therapy in patients not responding to other conservative modalities like anti-inflammatory drugs, physical therapy or occlusal splint therapy. 3 The procedure involves thorough irrigation of the upper joint compartment by the introduction of needles or cannulas into the TMJ.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In 2018, we had conducted a systematic review of such comparative studies but were able to include only five studies. 2 We had recommended further trials to explore the differences between the two techniques. By means of the current study, we aimed to update our previous review and compare intra-operative and postoperative outcomes between the two single-puncture and the standard double-puncture techniques of arthrocentesis.…”
Section: Introductionmentioning
confidence: 99%